Pengaruh Kesadaran Keamanan Informasi dan Privasi Jaringan Sosial Terhadap Perilaku Perlindungan Privasi pada Para Pengguna Jaringan Sosial - Chris, Novita (Universitas Teuku Umar, 2021)
Social networks are communication media that are used for sharing information and communicating. However, the popularity of social networks's user can not cover the anxiety about the privacy of user information data. This study aims to examine the factors that influence user anxiety about data security and security behavior. This study consists of five variables, namely response efficacy, self-efficacy, security awareness, and perceived security threat as an independent variable and internet user information privacy concern, and security behavior as the dependent variable. This study is a quantitative study that collects data and distributes questionnaires. The data in the study were analyzed through structural equation modeling (SEM) techniques with the help of SPSS. From the results of the study, this study proves that user perceptions of security threats (perceived security threats) have a significant effect on user anxiety about data privacy security when accessing social networks (Internet Users' Information Privacy Concern). This research provides insight to social network users to be more selective in managing data information security in providing personal data and taking protective actions against security behavior.